#TITLE_ALTERNATIVE# - YUNAZWARDI (NIM. 15106036); Pembimbing: DR. Irwan Meilano, S.T., M.Sc. dan Estu Kriswati, S., MUTIARA
Talang volcano is one of volcanoes located in the West Sumatera. The last magmatic eruption happened in 1883. The currently eruption was freatic eruption which happened in 2005. This eruption occurred in few days after tectonic earthquake in Mentawai in the same year. After that, TalangÃ‚Â’s volcanic activity had increased, meanwhile there are no significant eruptions. In order to analyze about the deformation which occurred in Talang along 2005-2009, the Global Positioning System (GPS) data from December 2005, March 2006, February 2007, February 2008, July 2009, August 2009, dan October 2009 surveys have been processed. From GPS data, geocentric and geodetic coordinates with the standard deviations could be resulted. The geocentric coordinates were transformed to topocentric coordinates. After the velocity rate from topocentric coordinate have been accepted by Student (t) distribution statistical testing , then the displacements would be plotted. Mogi model was used to calculate the location of magma pressure and the preffered result would be choiced by using optimation method.